Connexin 43 expression predicts poor progression-free survival in patients with non-muscle invasive urothelial bladder cancer. Issue 10 (6th August 2015) - Poyet, Cédric; Buser, Lorenz; Roudnicky, Filip; Detmar, Michael; Hermanns, Thomas; Mannhard, Doris; Höhn, Andrej; Rüschoff, Jan; Zhong, Qing; Sulser, Tullio; Moch, Holger; Wild, Peter J
Abstract : Objectives: To evaluate the protein expression of connexin 43 (Cx43) in primary urothelial bladder cancer and test its association with the histopathological characteristics and clinical outcome. Methods: A tissue microarray containing 348 tissue samples from 174 patients with primary urothelial carcinomas of the bladder was immunohistochemically stained for Cx43. The intensity of staining was semiquantitatively evaluated (score 0, 1+, 2+), and the association with clinicopathological features was assessed. Univariable and multivariable analyses were performed to identify predictors for progression-free survival (PFS). Results: Membranous Cx43 immunoreactivity was detected in 118 (67.8%) of 174 analysable urothelial carcinomas, of which 31 (17.8%) showed even a strong (score 2+) and mainly homogeneous staining. Strong expression levels of Cx43 (score 2+) were associated with higher tumour grade, multiplicity and increased proliferation (all p<0.05). In the subgroup of patients with stage pTa and pT1 bladder tumours (n=158), strong Cx43 expression (p<0.001), solid growth pattern (p<0.001) and increased Ki-67 proliferation fraction (p<0.05) were significantly associated with shorter PFS in an univariable Cox regression analysis. In multivariable Cox regression models, Cx43 immunoreactivity and histological growth pattern remained highly significant and adverse risk factors for PFS. Conclusions: The expression levels of Cx43 are frequent in non-muscle invasive bladder cancer (NMIBC), with high expression levels being associated with poor prognosis. Routine assessment of Cx43 expression may improve the identification of high-risk NMIBC.